Congenital fetal neck anomaly—diagnostic and therapeutic dilemma in low-resource setting: case report - Noel Yotamu, MD, MBBS; Chikondi Chiweza, MD, MMED; Kelli D. Barbour, MD, MSc, MA (AJOG Global Reports, 2023)
Fetal neck masses are uncommon but challenging to manage, particularly in limited-resource settings. We prenatally diagnosed a large fetal neck mass after consultative referral for polyhydramnios at 30 weeks’ gestation. The pregnant patient was counseled on the findings, differential diagnoses, and the prenatal and postnatal management options. She delivered at 38 weeks’ gestation through emergent cesarean delivery after presenting in labor owing to concern for labor dystocia with the large mass. The diagnosis of lymphangioma was made postnatally through imaging. Good prognosis has been reported in several cases with surgery and/or sclerotherapy, even in low-resource settings. Despite the availability of a pediatric surgeon to perform a resection, the family declined treatment because of a belief that the mass was of supernatural etiology. Patient-centered, multidisciplinary services focusing on maternal and fetal complications should assess and account for cultural beliefs to better understand and counsel families who have a fetus or neonate with a congenital anomaly.